HUBUNGAN ANTARA PENGUNGKAPAN, INFORMASI ASIMETRI DAN BIAYA MODAL - Muhammad Nuryatno; Nazmel Nazir; Maya Rahmayanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
This study intends to investigate the relationship between disclosure, asymmetryinformation and cost of capital. The samples of this study cover about 40 manufacturer companies listed at the Jakarta Stock Exchange in 2004 that selected using purposive random sampling. The analysis method used to test is simple regression, Kolmogorov-Smirnov and P-Plot. The study result were as follows, first hypothesis show there is no relationship between disclosure and asymmetry information. Second hypothesis result show that there is a positive relationship between asymmetry information and cost of capital. Third hypothesis, there is a relationship between disclosure and cost of capital.